2004
DOI: 10.1016/j.ccm.2004.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Cryptogenic organizing pneumonia

Abstract: Cryptogenic organizing pneumonia is a rare, distinct disorder that is sufficiently different from the other diseases in the group of idiopathic interstitial pneumonias to be designated as a separate entity. In its most typical presentation, it is characterized by dyspnea and cough, with multiple patchy alveolar opacities on pulmonary imaging. Definite diagnosis is obtained by the finding of buds of granulation tissue in the distal airspaces at lung biopsy. No cause (as infection, drug reaction, or associated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
35
0
9

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 114 publications
3
35
0
9
Order By: Relevance
“…The systemic inflammation caused by OP could have an effect in different organs, including the cardiovascular system. 3 Our findings on the causes of death in patients with COP and SOP, with respiratory disease being the most common, are in agreement with those of Lohr et al 7 We found a low rate of mortality from the disease itself, but patients died from other respiratory causes and their underlying disease. It was common for patients in our study to have underlying lung disease when diagnosed with OP.…”
Section: Discussionsupporting
confidence: 92%
“…The systemic inflammation caused by OP could have an effect in different organs, including the cardiovascular system. 3 Our findings on the causes of death in patients with COP and SOP, with respiratory disease being the most common, are in agreement with those of Lohr et al 7 We found a low rate of mortality from the disease itself, but patients died from other respiratory causes and their underlying disease. It was common for patients in our study to have underlying lung disease when diagnosed with OP.…”
Section: Discussionsupporting
confidence: 92%
“…There may also be some other key features 12. Pathological findings compatible with COP are uniform recent visual changes without severe disruption of the lung architecture, a patchy and peribronchiolar distribution, lesions localised within the air spaces, foamy macrophages commonly seen in alveolar spaces, intraluminal buds of granulation tissue, severe fibrotic changes (which are unusual) and giant cells (which are rare), as well as no granulomas or vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and prevalence are unknown. It occurs in the fifth or sixth decade of life without gender preference and with no association with smoking habits 1012. The majority of patients are symptomatic until a few weeks before diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, airway fibrosis likely resembles fibrosis in other tissues, which, despite long held assumptions, may be reversible 24 25. In some settings, airways fibrosis does appear to resolve 26. In addition, the goblet cell metaplasia that is frequently present in patients with chronic bronchitis can reverse 27.…”
mentioning
confidence: 99%